PENGUJIAN BAKTERI ENDOFIT TERHADAP EFISIENSI HARA PADA PERTUMBUHAN TANAMAN LADA DI LAMPUNG / The Evaluation of Endophytic Bacteria Application on Nutrient Efficiency of Black Pepper Growth in Lampung - Gusmaini Gusmaini; Andriana Kartikawati; Hera Nurhayati (Jurnal Penelitian Tanaman Industri, 2019)
Black pepper (Piper nigrum L.) requires high nutrients to support its growth. The research was carried out to find an alternative way to reduce high nutrient requirements with the application of growth-promoting bacteria. The research was conducted at Natar Experimental Station, Lampung Assessment Institute for Agricultural Technology (AIAT), from January to December 2018. The study was undertaken in a randomized block design, arranged factorially, with 16 treatments and 3 replications. The first factor was endophytic bacteria application consisted of: without endophytic bacteria (B0), Ca2 endophytic bacterial isolates (B1), isolates combination A (Dj9 + Sa4 + Labt8 + Ldbp4) (B2), and isolates combination B (Sa8 + Sd10 + Labt1 + Ldbp9 (B3). The second factor was fertilizer application comprised of: without fertilizer (P0), 25% (P1), 50% (P2), and 75% (P3) of recommendation dosage (NPKMg: 12: 12: 17: 2). The recommended fertilizer dose was 200 kg/ha/year. The results showed that there was an interaction between endophytic bacteria and fertilizer in enhancing plant growth and NPK nutrient uptake of pepper at 11 months after planting. The combination of Ca2 endophytic bacteria and 75% NPK fertilizer recommendations enhanced plant growth by 19.5% for plant height, 34.3% for the number of nodes, and 16.8% for the number of branches, compared to that without endophytic bacteria application. However, the combination of B2 endophytic bacteria and 75% of NPK fertilizer recommendations showed the best result for biomass weight and nutrient uptake. Endophytic bacteria can improve the effectiveness of organic fertilizer usage to support sustainable agriculture.Keywords: Piper nigrum, nutrition, improvement, PGPB. AbstrakLada (Piper nigrum L.) merupakan tanaman yang memerlukan hara cukup tinggi untuk pertumbuhannya. Penelitian ini dilakukan sebagai upaya untuk mengurangi pemberian hara yang cukup tinggi yaitu dengan memberikan bakteri pemicu pertumbuhan. Penelitian telah dilakukan di Kebun Percobaan Natar BPTP Lampung, dimulai dari bulan Januari-Desember 2018. Penelitian menggunakan rancangan acak kelompok, faktorial, 16 perlakuan dan 3 ulangan. Perlakuan terdiri dari faktor pertama penggunaan bakteri endofit yaitu; tanpa bakteri endofit (B0), isolat bakteri endofit Ca2 (B1), isolat kombinasi A (Dj9+Sa4+Labt8+Ldbp4) (B2), dan isolat kombinasi B (Sa8+Sd10+Labt1+Ldbp9) (B3). Faktor kedua pemupukan anorganik yaitu; tanpa pupuk (P0), 25% (P1), 50% (P2), dan 75% (P3) dosis rekomendasi (NPKMg: 12:12:17:2). Dosis rekomendasi adalah 200 kg/ha/tahun. Hasil penelitian menunjukkan adanya interaksi antara bakteri endofit dan pupuk terhadap peningkatan pertumbuhan, dan serapan hara NPK pada tanaman lada berumur 11 bulan setelah tanam. Pemberian bakteri endofit dapat meningkatkan tinggi tanaman 19,5%, jumlah ruas 34,3%, dan jumlah cabang 16,8% pada kombinasi bakteri endofit B1 dibandingkan tanaman tanpa pemberian bakteri endofit dan 75% rekomendasi pupuk NPK. Namun kombinasi perlakuan terbaik untuk bobot biomas dan serapan hara adalah pada kombinasi perlakuan bakteri endofit B2 dan 75% rekomendasi pupuk NPK. Bakteri endofit dapat berfungsi sebagai pupuk hayati dan dapat mengefisienkan penggunaan pupuk buatan untuk pertanian berkelanjutan.Kata kunci: Piper nigrum, nutrisi, peningkatan,PGPB.